Respostas

2013-10-05T13:56:34-03:00
3 x^{2} +10x-8=0  a=3  b=10 c=-8
\\x= -b+- \sqrt{b ^{2}-4.a.c }         2.a

x= -10 +- \sqrt{100-12.-8}               6

-10-+ \sqrt{100+96}                6

x= -10+-  \sqrt{196}              6

x = -10 -14    =   -24 = x -4                  6       6

x=-10+14 =        +4 =    x^{2}   2
               6[/tex]         6                        3


x= -4  x^{2} = \frac{2}{3}

A melhor resposta!
  • Usuário do Brainly
2013-10-05T14:01:10-03:00
3x" + 10x - 8 = 0
delta= b" -4.a.c
delta= 10" - 4.3.(-8)
delta= 100 + 96
delta= 196

x = -b+_raiz delta / 2.a
x = - 10 +_ 14 / 6
x* e x**

x* = - 10 - 14 / 6
x* = - 24/6
x* = - 4

x** = - 10 + 14 / 6
x** = 4/6 (simplifique por 2)
x** = 2/3
1 5 1
qual é a solução ??
s = {-4, 2/3}
+ cadê a solução ???
obrigadoo